Influence of Maintenance and Repair of Axle Boxes on the Risks of Their Failure - S. V. Myamlin; L. A. Muradian; O. A. Shykunov; I. V. Pitsenko (Nauka ta progres transportu, 2022)
Purpose. The main purpose of the study is to identify the interconnection between the risks of failure of axle boxes of freight cars and the success of performing a complex task of maintenance and repair. To do this, one should identify the sequence of calculating the values of successful completion of the complex task of maintenance and repair of freight cars, make practical calculations using the example of car repair companies of Prydniprovska Railway regional branch and identify the dependencies of failure risks of the freight cars and the process of successful completion of the task. Methodology. The paper constructs the interconnections of the probabilities of performing and not performing a complex task of maintenance and repair of freight cars. In addition, the calculation sequence of static probability estimates of successful performing and not performing of the set task, static estimates of the average deviation time and the main time of successful performing, as well as its intensity is presented. Findings. The obtained statistical data of the effective implementation of the complex task of maintenance and repair of freight cars at Prydniprovska Railway regional branch and the results of their empirical distribution throughout a period of 90 days, showed that the sample average is 24.1078 cars, the sample variance is 3.28 cars, the value of the standard deviation is 1.81 cars, and the coefficient of variation is 0.075 cars. The influence of diagnostics on the failure risks of axle boxes of freight cars during operation after fulfilling the task of maintenance and repair is also established. Originality. Based on statistical processing of experimental data, for the first time an empirical distribution of statistical data of successful completion of a complex task of maintenance and repair of freight cars was performed, which allows calculating the reliability indicators of axle boxes after maintenance and repair of freight cars. For the first time, the dependence of axle boxes diagnostics on the risk of failure of performing the task of maintenance and repair of freight cars is received, which will allow reducing the risk of failure if the task is successfully completed. Practical value. The use of diagnostics of axle boxes of freight cars during maintenance and repair can reduce the risk of failure by 2… 4.5 times.